Implementing Governance in Madrasah Leadership: An Analysis Based on the Regulation of the Minister of Religious Affairs Number 24 of 2018 - Basir, Marni; Kamus, Kamus; Kurniawan, Rahmat; Jannah, Saadal; Nurauliah, Nurauliah (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2025)
This article examines the implementation of madrasah principal governance based on Regulation of the Minister of Religious Affairs Number 24 of 2018 in Majene Regency, focusing on planning, implementation, evaluation, and its impact on educational quality. The study employed a qualitative multi-site design involving six public and private madrasahs at the MI, MTs, and MA levels. Data were collected through observation, interviews, and documentation. Informants included the Head of the Majene Regency Office of the Ministry of Religious Affairs, the Head of the Madrasah Education Section, the Chairperson of the Supervisory Working Group, madrasah supervisors, and madrasah principals. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña through data condensation, data display, and conclusion drawing and verification. The findings show that the regulation provides a clear legal framework and recruitment mechanism. However, regulatory dissemination, competency development, and principal performance evaluation have not been implemented evenly, particularly in private madrasahs. Public madrasah principals are recruited through open competitive selection, while private madrasah principals are appointed by foundations in coordination with the Ministry of Religious Affairs. Competency development involves collaboration among provincial and regency religious affairs offices and the Makassar Religious Training Center, but it has not reached all principals equally. The implementation of principal performance assessment is also inconsistent. Overall, the regulation has contributed positively to leadership governance and educational quality, although disparities between public and private madrasahs remain.